IKLIM KERJA ETIS MEMODERASI PENGARUH PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN - Diantara, I Kadek Agus; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2017)
Budgetary slack is the difference between the resources that are actually needed to complete the work effectively with a number of resources that were added to complete the task. This study aims to obtain empirical evidence on the effect of budgetary participation and budgetary slack ethical work climate in relation budgetary participation on budgetary slack. The data collection in this study using a survey method with questionnaire instrument. The population used in this study are 20 star hotel in the Ubud area. The samples were analyzed by 80 respondents using purposive sampling method of sampling. The analysis technique used in this study is Moderated regression analysis (MRA). The research proves the level of participation in the budget penyusunanan budgetary slack levels will decline. Then if the ethical work climate that is owned by managers during the budget process experienced an increase in the budgetary slack will experience a decline.
Keywords: participation budgeting; budgetary slack; ethical work climate